The determinants of tax revenue and tax effort in developed and developing countries: Theory and new evidence 1995-2015 - Marcelo Piancastelli; A.P. Thirlwall (University of Kent, School of Economics, 2019)
This paper measures the tax effort of a sample of fifty-nine developed and developing countries over the period 1995-2015 by comparing a country's actual tax/GDP ratio with the ratio predicted derived from an international tax function which relates tax revenue to various measures of a country's taxable capacity such as the level of per capita income; the share of trade in GDP; the productive structure, and the level of financial deepening. The tax function is estimated using cross section data; pooled time series/cross section data, and panel data using a fixed effects estimator. The results are compared and show a range of tax effort from South Africa with the highest effort and Switzerland with the lowest effort. Implications for policy are drawn.
Keywords: H2; 330; Tax ratios; tax effort